The Effect of Health Education Using the SOBAT TB Media on Tuberculosis Knowledge Among Vocational High School Adolescents: Pengaruh Edukasi Kesehatan Menggunakan Media Sobat TB terhadap Pengetahuan Tuberkulosis pada Remaja SMK - Banowati, Lilis; Wanti, Anika; Sirait, Healthy Seventina; Herlinawati, Herlinawati; Kurniasih, Uun; Firmansyah, Firmansyah (Journal of Society and Development, 2025)
Amid rapid technological advancement and the persistent global challenge of tuberculosis prevention, adolescents remain a vulnerable group often overlooked in promotive and preventive health efforts. Based on this phenomenon, this study aims to evaluate the effect of health education using SOBAT TB (Solusi Online Berbagi Informasi TBC) media on tuberculosis knowledge among Grade X students at SMK Bina Bangsa Sedong, Cirebon Regency, in 2025. This research employed a pre-experimental design with a one-group pretest-posttest approach, involving 68 respondents selected through total sampling. A questionnaire was administered before and after the educational intervention, and data were analyzed using the Paired T-Test. The results showed a significant increase in the average knowledge score from 40.74 to 73.46, with a p-value of 0.000 (p < 0.05), indicating the effectiveness of the SOBAT TB media intervention. The study concludes that SOBAT TB is effective in significantly improving adolescents' knowledge about tuberculosis. This study contributes to the growing evidence that contextual and youth-friendly digital health education media can serve as innovative, effective, and sustainable strategies in tuberculosis control efforts, particularly within educational settings.